Reproductive incompatibility and fitness components in Neoleucinodes elegantalis races (Lepidoptera, Crambidae) from three Solanaceae hosts - Ana Elizabeth Díaz-Montilla; Nathalie Baena-Bejarano; Clara Ines Saldamando; James Montoya-Lerma (Caldasia)
Neoleucinodes elegantalis (Lepidoptera, Crambidae) is a Neotropical Solanaceae pest that has evolved into four host races due to host plant association. In this study, prezygotic and postzygotic isolation were evaluated in parental and F1 generations collected from Solanum lycopersicum (S. l), S. quitoense (S. q) and S. betaceum (S. b), representing medium size (S. l, S. q) and large size genitalia races (S. b). 617 adults were obtained in the laboratory and 106 copulated. One spermatophore per female was found in the bursa copulatrix, suggesting monoandry. Crosses between adults mostly occurred assortatively. A third of the female’s eggs laid occurred, but females from ♀S. b x ♂ S. l, ♀S. l x ♂S. b and S. l x S. l did not. In the cross, ♀S. l x ♂ S. q and its reciprocal F1 progeny developed into larvae. Reproductive success only occurred in three crosses: S. q x S. q, ♀ S. q x ♂ S. b and its reciprocal progeny. All the progeny from these crosses reached adulthood. The parental population showed differences in pupae and adult measurements according to host. The results on reproductive isolation obtained here suggest speciation in N. elegantalis due to host race differentiation which is relevant for the improvement of the management of this species, especially when the species has evolved reproductive isolation among races. We suggest that the use of their host plants in sympatry might reduce N. elegantalis densities in the field since hybrids between its races have low survival rates and to evaluate the possibility of pheromone composition differentiation among races given the results on assortative mating obtained here.